Hypertension and its risk factors among pregnant garment workers attending a health centre in Bangladesh - Khatun, Tayeba; Arifa Akter; Mahesh Kumar Khanal; Zahid Arefin; Bhuiyan, Rijwan (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: The burden of hypertension among the pregnant garment workers in Bangladesh is not well known. The aim of this study was to determine the prevalence of hypertension and its associated factors among pregnant garment workers attending a health centre in Narayanganj, Bangladesh. Methods: A cross-sectional study was done among conveniently selected adult pregnant garment workers at ≥20 weeks of gestation who visited a health centre of a garment company in Narayanganj, Bangladesh, between July and October 2023. Data on age, education, job nature, family history, clinical, height, weight, and blood pressure were collected. Binary logistic regression was performed to identify factors associated with hypertension. Results: Of 150 participants the average age was 27.3 years (standard deviation, 3.2) and mean gestational age was 21.7 weeks. The prevalence of hypertension among the participants was 7.3% (95% confidence interval, 4.0% - 12.3%). A family history of pregnancy-related hypertension was found to be associated with hypertension (adjusted odds ratio, 34.7; 95% confidence interval, 2.0 - 619.0). Conclusion: Approximately one in 14 pregnant garment workers had hypertension, and family history of pregnancy-related hypertension was an associated factor. Healthcare professionals may consider this factor while providing care and counseling to this population.